Molecular Design Principles for Near‐Infrared Absorbing and Emitting Indolizine Dyes. Issue 43 (13th September 2016) - Huckaba, Aron J.; Yella, Aswani; McNamara, Louis E.; Steen, April E.; Murphy, J. Scott; Carpenter, Casey A.; Puneky, George D.; Hammer, Nathan I.; Nazeeruddin, Mohammad Khaja; Grätzel, Michael; Delcamp, Jared H.
Abstract: Desirable components for dye‐sensitzed solar cell (DSC) sensitizers and fluorescent imaging dyes include strong donating building blocks coupled with well‐balanced acceptor functionalities for absorption beyond the visible range. We have evaluated the effects of increasing acceptor strengths and incorporation of dye morphology controlling groups on molar absorptivity and absorption breadth with indolizine donor‐based dyes. Indolizine‐basedD –A andD –π–A sensitizers incorporating bis‐rhodanine, tricyanofuran (TCF), and cyanoacrylic acid functionalities were analyzed for performance in DSC devices. The TCF derivatives were also evaluated as near‐infrared (NIR)‐emissive materials with theAH25 emissions extending past 1000 nm. Abstract : Donor design : Indolizine‐based D–A and D–π–A dyes with variable acceptor strength were evaluated as sensitzers for dye‐sensitized solar cells and as near‐infrared emissive materials. The charge‐transfer absorption band energy was lowered and significantly broadened by increasing the acceptor strength and inclusion of a π‐bridge.